2013
DOI: 10.1073/pnas.1301733110
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effects of group size on collective action and resource outcomes

Abstract: For decades, scholars have been trying to determine whether small or large groups are more likely to cooperate for collective action and successfully manage common-pool resources. Using data gathered from the Wolong Nature Reserve since 1995, we examined the effects of group size (i.e., number of households monitoring a single forest parcel) on both collective action (forest monitoring) and resource outcomes (changes in forest cover) while controlling for potential confounding factors. Our results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 51 publications
8
101
3
Order By: Relevance
“…A previous study by our research group has found that panda habitat (for which forest cover is essential), recovered faster in household monitored parcels than in government monitored parcels, after controlling for other contextual factors (e.g., elevation, slope, aspect, distance to the main road) (Tuanmu, 2012). We have also found that the effects of group size (i.e., the number of households for monitoring a forest parcel) on household monitoring efforts and forest outcomes are nonlinear, with intermediate group size (i.e., 9 in a range from 1 to 16 households) performing the best (Yang et al, 2013c). The optimum group size also shifts with context.…”
Section: Lessons Learned Through Nfcp Implementation In Wolong Naturementioning
confidence: 85%
See 4 more Smart Citations
“…A previous study by our research group has found that panda habitat (for which forest cover is essential), recovered faster in household monitored parcels than in government monitored parcels, after controlling for other contextual factors (e.g., elevation, slope, aspect, distance to the main road) (Tuanmu, 2012). We have also found that the effects of group size (i.e., the number of households for monitoring a forest parcel) on household monitoring efforts and forest outcomes are nonlinear, with intermediate group size (i.e., 9 in a range from 1 to 16 households) performing the best (Yang et al, 2013c). The optimum group size also shifts with context.…”
Section: Lessons Learned Through Nfcp Implementation In Wolong Naturementioning
confidence: 85%
“…Moreover, the main activities responsible for deforestation in the reserve (i.e., logging and fuelwood collection) have been reduced due to the implementation of NFCP (see Section 3.2 below). Our previous studies (Tuanmu, 2012;Viña et al, 2011;Yang et al, 2013c) also suggest that the NFCP has been a major driving force of forest change in the reserve and surrounding areas since 2001. Viña et al (2011) indicated that NFCP together with GTGP led to the forest transition in Wenchuan County, from a net forest loss in 1990s to a net forest increase from to 2007.…”
Section: Baseline For Environmental Benefitsmentioning
confidence: 99%
See 3 more Smart Citations